From descriptivism to constructivism – a challenge to symbolic modeling. I - Kjellman, Arne (Mathematical Modelling and Analysis, 1998)
Classical modeling is not isomorphic, on the contrary the “objects of reality” or the like is the source of a homomorphic mapping performed to produce the model – just the way a piece of landscape is portrayed by its map with some bewildering details left out. We are thus taught that this process of modeling (or abstraction) is a plain mapping procedure ‐ we call this descriptivism or representationalism. The prevailing object‐oriented modeling approach ‐ or realistic approach ‐ has some serious shortcomings due to the negligence of some aspects of the observer function, which for instance has resulted in a “world definition” made from “outside” the living consciousness (realism or materialism). By reversing this picture instead taking off from the impressions arisen within the subject's (the observer/knower's) conscious experience ‐ the subject‐oriented approach ‐ and ask how a living consciousness organize s itself to handle the task of living, we gain new insights in the process of conceptualization and learning. We learn that the dualistic worldview is superfluous and should better be replaced by a neutral monistic approach, where the hypothetical existence of an independent outside reality (realism) can be substituted by the idea of a reality constructed from inside a living consciousness ‐nothing else but a model whose main purpose is to guide human anticipation and facilitate communication. Taking that stances the main tasks of human consciousness just become modeling ‐ creating the outside model reality and th e inside domain of feelings. In such a framework also the classical truth ‐ in the sense of a God‐given modeling truth become meaningless ‐ and must be substituted by the Pierce‐ain pragmatical or consensual truth. In the subject‐oriented approach states, properties etc. are not given any observer independent existence. On the contrary they emerge at the moment of their measurement as advocated by the Copenhagen interpretation. Bell's theorem also states: Given the quantum mechanics, either the idea of Einstein locality or the idea of an observer independent reality must be abandoned. The subject‐oriented approach clearly abandons the idea of a pre‐given observer independent reality ‐ in favor of a cognitive agent created private reality, which then become the base for defining an “objective reality” in the form of a consensual scientific agreement.First Published Online: 14 Oct 2010